Den reaktionære tanke - Thorup, Mikkel (K&K - Kultur og Klasse, 2018)
This article explores the basic arguments of reactionary thinking. I argue that reactionary thought originates in an opposition to the Enlightenment and stayed fairly consistent since then, though with local variations around the core. The article first discusses a number of books on reactionary thought before developing the thesis of the genesis of reactionary thought in and around the Enlightenment, not least the opposition to the idea of man as the sovereign creator of his or her own destiny. Then it goes into detail on the specifics of reactionary thought before ending with a few reflections on the contemporary version of reactionary thought.